Implications of Parental Support on Children’s Al-Qur’an Learning at TPQ Muhajirin, Bumi Ayu Village, Selebar District, Bengkulu City - M. Gilang; Evi Asmara; Melanda; Salsadila Dwi Parica; Sintia Dwi Anjani; Kurniawan (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Al-Qur’an learning for early childhood is an important foundation in the formation of religious character. TPQ Muhajirin in Bumi Ayu Village, Selebar District, Bengkulu City has great potential in the form of high student learning enthusiasm and strong community support, but parental involvement in the learning process is still not optimal. This community service aims to increase parental involvement in supporting children’s Al-Qur’an learning through an Asset-Based Community Development (ABCD) approach. The method used includes four stages: Discovery (community asset mapping), Dream (shared vision exploration), Design (participatory program design), and Destiny (implementation and sustainability commitment). The results show a significant increase in the frequency of parental assistance at home by 72%, an increase in student attendance by 18%, and the formation of an active community of parents who care about TPQ. The Societal Impact Index analysis from the satisfaction questionnaire shows an average score of 4.3 on a scale of 5.0, indicating a positive and measurable social impact. The conclusion of this community service affirms that the community strength-based ABCD approach is able to mobilize active parental participation, thereby impacting the improvement of the quality of children’s Al-Qur’an learning at TPQ Muhajirin on a sustainable basis.